Winery Names of Northern Greece and Their Contribution to Wine Communication Strategies - Theodosios Tsiakis; Eleni Anagnostou (Beverages)
When it comes to wine communication, winery names can serve as multidimensional communication mechanisms. Their various aspects of communication concern the historical context, tourism geography, socio-economic tourism development, wine knowledge, and even gastronomy. On this basis, a whole communication strategy could be developed, which could lead to progressive interaction and networking with consumers. Quality needs to be fully and properly communicated through multiple channels. This paper aims to reveal the importance of the way in which wine producers in Northern Greece construct their brand identity through strategic naming choices—such as Estate, Ktima, Château, or the producer’s family name—as opposed to more neutral or descriptive labels. The findings suggest that winery names contribute significantly to consumer perception, place branding, and the development of wine tourism. The choice of a winery name influences regional identity, strengthens the connection with local traditions, and enhances the commercial success and tourism appeal of the region.